Tip-Cylinder Electrode Plasma to Enhance the Coating of Conductive Yarn Process - Valentinus Galih Vidia Putra; Lutfi Zulfikar; Atin Sumihartanti; Juliany Ningsih Mohamad; Yusril Yusuf (Jurnal Rekayasa Proses, 2020)
This study aims to develop conductive textile materials using a polyester textile yarn by applying a knife coating method and pre-treatment of a tip-cylinder plasma electrode. In this research, carbon ink was coated on polyester staple yarn which was given a pre-treatment with a plasma generator and coated with the knife coating method. The electrical conductivity of conductive yarns produced from this study was divided into two types, as yarns without plasma treatment and with plasma treatment with a ratio of water and carbon ink concentrations of 1:1 and 2:1. The results of the electrical conductivity with plasma treatment and the concentration of carbon ink and water of 1:1 and 1:2 were 69005 (Ωm)-1 and 50144.25 (Ωm)-1, respectively, while the results of the electrical conductivity for threads with concentrations of carbon ink and water of 1:1 and 1:2 without plasma treatment were 18197.64 (Ωm)‑1  and 8873.54 (Ωm)-1, respectively. The results showed that the concentration of carbon ink and water and plasma treatment affected the conductive value of the yarn. The results also showed that the presence of plasma pre-treatment improved the coating process of conductive ink on the yarn.Keywords: carbon ink; conductive yarn; plasma; textile A B S T R A KPenelitian ini bertujuan untuk mengembangkan bahan tekstil konduktif menggunakan benang tekstil poliester dengan mengaplikasikan metode knife coating dan pre-treatment plasma elektroda tip-cylinder. Pada penelitian ini dilakukan pelapisan dengan tinta karbon pada benang poliester stapel yang diberi perlakuan awal dengan plasma generator dan dilapisi dengan metode pelapisan knife coating. Konduktivitas listrik benang konduktif yang dihasilkan dari penelitian ini dibagi menjadi dua jenis, yaitu benang tanpa perlakuan plasma dan dengan perlakuan plasma dengan perbandingan konsentrasi air dan tinta karbon sebesar 1:1 dan 2:1. Hasil konduktivitas listrik dengan perlakuan plasma dan konsentrasi tinta karbon dan air sebesar 1:1 dan 1:2 masing-masing adalah 69005 (Ωm)‑1 dan 50144,25 (Ωm)-1, sedangkan hasil konduktivitas listrik untuk benang dengan konsentrasi tinta karbon dan air sebesar 1:1 dan 1:2 tanpa perlakuan plasma masing-masing adalah 18197,64 (Ωm)-1 dan 8873,54 (Ωm)-1. Hasil penelitian menunjukkan bahwa konsentrasi tinta karbon dan air serta perlakuan plasma berpengaruh terhadap nilai konduktivitas benang serta adanya pre-treatment plasma dapat meningkatkan proses coating tinta konduktif pada benang.Kata kunci: benang konduktif; plasma; tekstil; tinta karbon